Microparticles Mediate the Intercellular Regulation of microRNA-503 and Proline-Rich Tyrosine Kinase 2 to Alter the Migration and Invasion Capacity of Breast Cancer Cells - Gong, Joyce; Luk, Frederick; Jaiswal, Ritu; Bebawy, Mary (Frontiers in Oncology, 2014)
The successful treatment of cancer is hampered by drug resistance and metastasis. While these two obstacles were once considered separately, recent evidence associates resistance with an enhanced metastatic capacity. However, the underlying mechanisms remain undefined. We previously described the intercellular transfer of drug resistance via submicron vesicles called microparticles (MPs). We now propose that MPs derived from drug-resistant cells are also involved in the intercellular transfer of metastatic traits, making MPs a conduit between resistance and metastasis. We used microarray analysis to identify regulatory microRNAs (miRNAs) which contribute to the dissemination of metastatic traits. miR-503 was downregulated in recipient cells following co-culture with MPs isolated from drug resistant cells. miR-503 was inversely associated with metastasis, as demonstrated using wound healing/scratch migration assays and Matrigel®-coated transwell invasion assays. Proline-rich tyrosine kinase 2 (PYK2) was upregulated in recipient cells and associated with increased migration and invasion, with these phenotypes being reversed using a pharmacological inhibitor of PYK2 phosphorylation, tyrphostin A9. However, the MP-mediated promotion of metastatic traits was not due to the presence of these effectors in the MP cargo but rather due to down stream effector molecules in these pathways. This is the first demonstration that the role of MPs in trait acquisition extends beyond the direct transfer of vesicle components and also includes transfer of intermediary regulators that induce down stream mediators following transfer to recipient cells. This implicates an expanding role of MPs in cancer pathogenesis.